Community empowerment with moringa leaf-based food diversification for stunting prevention in the Sidosermo Community Health Center, Surabaya - Juliana Christyaningsih; Melina Sari; Khristine Saputri; Husnul Halimah; Meisya Argia Sisviani Deva; Pojor Srirejeki Eka Lestari; Muna Setia Madihah (Community Empowerment, 2023)
Based on Riskesdas data in 2018, the height of children under 2 years old in the very short (stunting) and short categories is 29.9%. Puskesmas cadres as partners, play an active role when participating in socialization of the Community Service program and counseling on the benefits of consuming moringa leaves and fish in an effort to prevent stunting. 10 cadres participated in the activity and produced 24 recipes for dry snacks made from moringa leaves and fish. In addition, 5 cadres have followed up this program by processing PIRT permits.